Normalization and Commodification of the Body and Sexuality in Kim Kardashian and Kylie Jenner’s Instagram Posts - Leiliyanti, Eva; Chaerunnisa, Sabilla; Diyantari, (International Journal of Psychosocial Rehabilitation, 2020)
As global influencers, Kim Kardashian and Kylie Jenner are not merely in a subject-object hegemonic discourse and in a discipline of their body and sexuality, but they also monetize from commodification of their body and sexuality through Instagram posts. Fuelled by the advanced internet celebrity phenomenon and capitalism, this study aims at dismantling and seeing the extent Kim and Kylie’s photos and captions reveal the process of normalization of the body and sexuality based upon Kress and van Leeuwen’s social semiotics and Halliday’s transitivity system from the structuralist viewpoint. In dismantling the process of normalization, Foucauldian panopticism and Baudrillardian hyperreality were deployed in the study. The results revealed that during the process of normalization, Kim and Kylie were under constant surveillance and were monitored by a capitalist system, the viewers and themselves demanding their body and sexuality being exposed in a public sphere at all times—on Instagram—through applying revealing fashion style as well as other seductive attributes, poses, and gestures to the body. Each Instagram post emerged only as a simulation of a new set of unattainable standards appeared on digital media—on their Instagram posts, rather than the ‘real’ self-representation of Kim Kardashian and Kylie Jenner. Three out of four Instagram posts of Kim and Kylie showed no connection between the products being advertised on the caption and the focus elements on the image—their revealing body and sexuality. Kim and Kylie’s inner lust and sexual appeal which were emanated from their body had been commodified.